PEMBUDAYAAN LITERASI DIGITAL DALAM PEMBELAJARAN BAHASA INDONESIA SEKOLAH DASAR - Khosiah Widi Astuti; Sutama (JS (JURNAL SEKOLAH), 2026)
Abstract: The era of Society 5.0 demands digital literacy as an important skill in education, especially in Indonesian language learning in elementary schools. This study aims to (1) describe the cultivation of ethical and security aspects in digital information access, and (2) explore the cultivation of ethical and security aspects in the application of digital literacy in Indonesian language learning in elementary schools. This study uses a qualitative approach with an ethnographic type. The research subjects include the principal, Indonesian language teachers, and fifth-grade students at the elementary school where the research was conducted. Data collection techniques were carried out through interviews, observations, and document analysis. Data validity was obtained through source and method triangulation, while data analysis was conducted inductively. The results of the study show that (1) the cultivation of ethics and security in the aspect of digital information access is reflected in the students' ability to access digital learning resources independently with the guidance of teachers using school devices, and (2) the cultivation of ethics and security in the aspect of application is demonstrated through the students' vigilant and responsible attitude in using digital media, especially in maintaining the privacy of personal data. The conclusion of this study shows that the cultivation of digital literacy ethics and security can shape students who are responsible in learning, able to collaborate online and offline, and have an initial awareness of creating and utilizing digital content safely, creatively, and innovatively. Keyword: security ethics, digital literacy, Indonesian language learning, elementary school Abstrak: Era Society 5.0 menuntut literasi digital sebagai keterampilan penting dalam pendidikan, khususnya pada pembelajaran Bahasa Indonesia di sekolah dasar. Penelitian ini bertujuan untuk (1) mendeskripsikan pembudayaan aspek etika dan keamanan dalam akses informasi digital, serta (2) mengeksplorasi pembudayaan aspek etika dan keamanan dalam penerapan literasi digital pada pembelajaran Bahasa Indonesia di sekolah dasar. Penelitian ini menggunakan pendekatan kualitatif dengan jenis etnografi. Subjek penelitian meliputi kepala sekolah, guru Bahasa Indonesia, dan siswa kelas V di sekolah dasar tempat penelitian. Teknik pengumpulan data dilakukan melalui wawancara, observasi, dan analisis dokumen. Keabsahan data diperoleh melalui triangulasi sumber dan metode, sedangkan analisis data dilakukan secara induktif. Hasil penelitian menunjukkan bahwa (1) pembudayaan etika dan keamanan pada aspek akses informasi digital tercermin dari kemampuan siswa mengakses sumber belajar digital secara mandiri dengan bimbingan guru menggunakan perangkat sekolah, serta (2) pembudayaan etika dan keamanan pada aspek penerapan ditunjukkan melalui sikap waspada dan bertanggung jawab siswa dalam menggunakan media digital, khususnya dalam menjaga privasi data pribadi. Simpulan penelitian ini menunjukkan bahwa pembudayaan etika dan keamanan literasi digital mampu membentuk siswa yang bertanggung jawab dalam belajar, mampu berkolaborasi secara daring maupun luring, serta memiliki kesadaran awal dalam menciptakan dan memanfaatkan konten digital secara aman, kreatif, dan inovatif. Kata Kunci: Etika Keamanan, Literasi digital, Pembelajaran Bahasa Indonesia, Sekolah dasar